Special Economic Zones (SEZs) Impact on Poverty in Indonesia - Taufiqurrahman Taufiqurrahman; Khoirunurrofik Khoirunurrofik (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2023)
Special Economic Zones (SEZs) have been implemented in Indonesia to promote economic development and attract foreign investment. In economic literature, there is still debate, as the available literature still needs to provide a clear conclusion on how place-based policies such as SEZs can affect well-being. The synthetic control method is employed in this study to examine the impact of SEZs on poverty rates at both the district and city levels using data from 2005 to 2021. By delving into the relationship between SEZs and poverty, this study seeks to shed light on the effectiveness of SEZs in addressing poverty in local communities. It compares it with the counterfactual district/city, a synthetic of districts/cities that do not have SEZs in their region. The results of this study found that of the eight districts/cities that have SEZs, the existence of SEZs has a varying impact on poverty levels, with an increase in poverty in four districts/cities and a decrease in poverty in the other four districts/cities, the study also reveals the complexity of the social impacts of place-based policies like SEZs.